Pengaruh Terapi Okupasi: Hasta Karya terhadap Harga Diri pada Pasien Skizofrenia - Martini Puspita Yanti, Ni Made Yogi; Ari Kresna Dewi, Ni Luh Gede; Candra, I Wayan; Harini, I Gusti Ayu (Jurnal Gema Keperawatan, 2024)
Schizophrenia is a psychotic disorder that affects a person's ability to think, feel or behave properly. The negative symptoms that arise are low self-esteem problems where individuals always underestimate themselves and their abilities. Low self-esteem that continues can cause social interaction disorders, self-care deficits, anxiety disorders and non-compliance with treatment. One form of therapy to regain a person's self-confidence is through occupational therapy. The purpose of this study was to prove the effect of occupational therapy: hasta karya on self-esteem in schizophrenia patients at the Bali Provincial Mental Hospital in 2024. This research method uses a one-group pre-post test design. The sampling technique is non-probability sampling with purposive sampling. The number of samples is 30 respondents. The research instrument uses the Rosenberg Self-Esteem Scale (RSES). The normality test uses the Shapiro-Wilk test. Hypothesis testing uses the Wilcoxon Signed Ranks Test. The results showed that before being given occupational therapy: hasta karya, 30 people (100,0%) had low self-esteem. After the intervention, 20 people (66,7%) had moderate self-esteem and 10 people (33,3%) had low self-esteem. After analysis, the p-value = 0,000 alpha (0,05) was obtained, meaning that there was an effect of providing occupational therapy intervention: handicrafts on low self-esteem in schizophrenia patients at the Bali Provincial Mental Hospital in 2024, so it can be concluded that occupational therapy: handicrafts can increase self-esteem in schizophrenia patients.